Effect of Citronella (Cymbopogon nardus) Aromatherapy Inhalation on Hematology Profile in Mice (Mus musculus) - Shafa Azizah; Eko Fuji Ariyanto; Khairani, Shafia (Veterinary Biomedical and Clinical Journal, 2025)
Citronella (Cymbopogon nardus) is a widely distributed herbal plant throughout Indonesia, known for its aromatic essential oils that possess various biological properties such as antimicrobial, anti-inflammatory, and insect-repellent effects. Despite its widespread traditional use, limited studies have evaluated the systemic safety profile of citronella essential oil when administered via inhalation, especially its impact on hematological parameters, which are critical indicators of physiological and immune status. This study aimed to investigate the effects of inhaled citronella essential oil on the hematological profile of Swiss webster mice to assess its potential hematotoxicity and systemic safety. Citronella essential oil was extracted using steam-water distillation and characterized through phytochemical screening. Mice were divided into five groups: a negative control, a positive control treated with Diazepam (0.012 mg/kg), and three treatment groups exposed to citronella essential oil vapor for 30 minutes (P1), 60 minutes (P2), and 90 minutes (P3). Each dose consisted of 500 µL of essential oil diluted 1:1 with pyrogen-free water, corresponding approximately to 445 mg of essential oil per administration, with an estimated concentration of about 44.5% w/v based on typical oil density. Hematological parameters, including red and white blood cell counts, hemoglobin concentration, hematocrit, and platelet levels, were analyzed using the Kruskal-Walli’s test. The results showed no statistically significant differences between the citronella-exposed groups and controls, indicating that inhalation exposure at the given dose and duration did not induce hematological toxicity or adverse systemic effects. These findings suggest that citronella essential oil, when administered by inhalation under the tested conditions, is safe in Swiss webster mice and supports its continued use in aromatherapy and related applications. Further studies are recommended to explore long-term effects and other physiological parameters.